If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6b + 6 = 4b Reorder the terms: 6 + 6b = 4b Solving 6 + 6b = 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. 6 + 6b + -4b = 4b + -4b Combine like terms: 6b + -4b = 2b 6 + 2b = 4b + -4b Combine like terms: 4b + -4b = 0 6 + 2b = 0 Add '-6' to each side of the equation. 6 + -6 + 2b = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 2b = 0 + -6 2b = 0 + -6 Combine like terms: 0 + -6 = -6 2b = -6 Divide each side by '2'. b = -3 Simplifying b = -3
| 2+4+6+8+2n=27 | | 2x^2-1/2x=1/8 | | (42/2+60-8)+(61-8*3) | | 6g=-7+5g | | 8x+3=x-15 | | 1+3+5+7+9+(2n-1)=26 | | 6w=5w-9 | | x-3/2=1 | | 5x+10forx=12 | | 16d^2+40d+25=0 | | 8-7p=-8p | | 1+3+5+7+(2n-1)=26 | | 8s+13=-7s-13 | | 5x-(2/3)=4x+(4/3) | | 10t=-7t-6 | | 6x^4-48=0 | | 9+x1/6=-11 | | 5x-2/3=4x+4/3 | | 4+3a=a | | 12-z1/6=-2 | | 5=0.5s-15 | | 3p/8-16=-25 | | 3x-2(x+1)=7 | | 12x+9=-9x+15 | | 2+2w=P | | 12=4(3) | | p=2l+2 | | 14x+5=4x-8-(2x+4) | | -2+3s=99s+5 | | 2+x1/2=14 | | 8x-40=24 | | 8x-40=24 |